Proceedings of the International Seminar on Safety and Security of Autonomous Vessels (ISSAV) and European STAMP Workshop and C 2020
DOI: 10.2478/9788395669606-012
|View full text |Cite
|
Sign up to set email alerts
|

An initial hierarchical systems structure for systemic hazard analysis of autonomous ships

Abstract: Safety assurance of autonomous ships is one of the major long-term challenges faced by the maritime world. Applying systemic hazard analysis methods at this early stage will guide the design and operation of safe autonomous ships. This paper proposes an initial hierarchical ship systems structure that could be the basis for a systemic hazard analysis of autonomous ship systems and operations. The approach is based on the systems theory and the principle of hierarchy and has been developed via the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The potential of FRAM for the hazard analysis of autonomous ships has been discussed by several studies. Chaal et al [73] emphasized that that FRAM (together with STPA) can contribute to the safe deployment of autonomous ships. Basnet et al [74] concluded that FRAM and STPA can be optimal methods to analyze the hazards of complex and interconnected systems of autonomous ships, and Relling et al [75] argued that systemic safety models (like FRAM and STAMP) can be candidates for assessing safety in designing autonomous ships.…”
Section: Hazard Analysis For Massmentioning
confidence: 99%
“…The potential of FRAM for the hazard analysis of autonomous ships has been discussed by several studies. Chaal et al [73] emphasized that that FRAM (together with STPA) can contribute to the safe deployment of autonomous ships. Basnet et al [74] concluded that FRAM and STPA can be optimal methods to analyze the hazards of complex and interconnected systems of autonomous ships, and Relling et al [75] argued that systemic safety models (like FRAM and STAMP) can be candidates for assessing safety in designing autonomous ships.…”
Section: Hazard Analysis For Massmentioning
confidence: 99%